Pemberdayaan UMKM Seblak Cobek Teh Ida Braga Bandung melalui Pendampingan Analisis SWOT dalam Strategi Pengembangan Usaha - Ratna Nengsih; Nur Ria Azahra; Nabilah Siti Fadiyah; Ghefira Rhoudotul Jannah; Putri Nur Maulidya; Salsabila Azahra; Ridlwan Muttaqin (Pakis Journal Institute, 2026)
Within the modern economic framework, Micro, Small, and Medium Enterprises (MSMEs) serve as vital engines for driving financial growth and generating local employment. Nonetheless, these smaller enterprises frequently navigate a complex landscape marked by fierce market rivalry, evolving customer tastes, and rapid digital advancements. This empirical investigation centers on utilizing a SWOT matrix to formulate an optimal growth strategy for the Seblak Teh Ida Braga Bandung MSME. Methodologically, the project adopts a descriptive quantitative design, gathering primary data via direct observation, structural interviews, and archival documentation. The analytical framework categorizes internal capabilities alongside external environmental dynamics affecting the enterprise. The empirical findings reveal that Seblak Teh Ida Braga Bandung benefits from robust core strengths, including a unique flavor profile, budget-friendly pricing, and a highly accessible storefront location. Conversely, its operational vulnerabilities stem from inadequate online marketing and constraints in manpower. Externally, the business can capitalize on a rising consumer appetite for fiery culinary items and the expansive reach of social platforms for promotion. However, it must also counter substantial headwinds from market saturation by direct competitors and volatile consumer preferences. Ultimately, the strategic roadmap derived from this matrix highlights the necessity of upgrading digital outreach, preserving core product integrity, introducing innovative menu options, and widening market distribution to secure long-term viability and competitive advantage.